1998
DOI: 10.1182/blood.v92.4.1150
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Mycosis Fungoides/Sezary Syndrome: Clinical Characteristics and Prognosis

Abstract: The occurrence of large cell transformation has been well documented in a subgroup of patients with mycosis fungoides/Sezary syndrome (MF/SS). However, because of the rarity of MF/SS, little is known about the influence of clinicopathologic features in predicting large cell transformation and about outcome in the transformed cases. We evaluated all patients with MF/SS who were registered in our clinic during the study period and for whom pathologic slides for review were available or could be obtained. Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
1
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(98 citation statements)
references
References 22 publications
3
83
1
11
Order By: Relevance
“…In addition to staging, male gender, increasing age, an elevated LDH and the folliculotropic variant of MF were also independently associated with poorer overall and disease-specific survival. In contrast to previous reports highlighting the aggressive clinical course associated with large cell transformation, [141][142][143][144][145] defined as the presence of large, atypical lymphocytes comprising at least 25% of the total lymphoid infiltrate, large cell transformation was not an independent predictor of overall or disease-specific survival, but was associated with a higher risk (hazard ratio 3.32) of disease progression. 6 Given the importance of the TNMB classification in risk stratification and defining disease burden, the ISCL/EORTC recommends its use in defining the initial, maximum and current burden of disease, which will ultimately play an important role in the selection of either skin-directed or systemic therapies.…”
Section: Stagingcontrasting
confidence: 88%
“…In addition to staging, male gender, increasing age, an elevated LDH and the folliculotropic variant of MF were also independently associated with poorer overall and disease-specific survival. In contrast to previous reports highlighting the aggressive clinical course associated with large cell transformation, [141][142][143][144][145] defined as the presence of large, atypical lymphocytes comprising at least 25% of the total lymphoid infiltrate, large cell transformation was not an independent predictor of overall or disease-specific survival, but was associated with a higher risk (hazard ratio 3.32) of disease progression. 6 Given the importance of the TNMB classification in risk stratification and defining disease burden, the ISCL/EORTC recommends its use in defining the initial, maximum and current burden of disease, which will ultimately play an important role in the selection of either skin-directed or systemic therapies.…”
Section: Stagingcontrasting
confidence: 88%
“…In our series median delay from the initial diagnosis of MF to documentation of the onset of large-cell transformation was 3AE6 years (range 1-115 months) (12 months in Diamandidou et al 13 ) (Table 1). We also observed that fatal cases had a relatively shorter delay from initial diagnosis of MF to transformation.…”
Section: Discussionmentioning
confidence: 56%
“…Chromosomal rearrangement, 10 expression of CD25 antigen (interleukin 2 receptor), 11 Recent studies in a group of 26 13 cases and in a series of 45 14 patients with T-MF showed conflicting data about clinical features associated with a poor outcome. In the first study, 13 poor survival is associated with early transformation (< 2 years after initial diagnosis of MF) and advanced clinical stage at the time of T-MF (IIB-IV vs. I-IIA). In the second study, 14 older age ( ‡ 60 years) and extracutaneous invasion (stage IV) were found to be correlated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 T-cell receptor (TCR) genes are clonally rearranged in the peripheral blood, skin and lymph nodes. 9,10 Unusual and rare features of SS include its association with monoclonal gammopathies or myeloma [11][12][13][14] or other B-cell proliferations, 15 development of granulomatous lesions, [16][17][18] association with myelodysplastic syndrome (MDS), [19][20][21] transformation into a high-grade malignant lymphoma, [22][23][24][25] and development of various secondary neoplasms. 26 We report a patient with SS, who developed several unusual features during the course of the disease, namely granulomatous lesions harbouring dominant T-cell clone, transformation into CD30-positive largecell pleomorphic T-cell lymphoma, and MDS.…”
mentioning
confidence: 99%